Monatomic cobalt-doped carbon fiber material as well as preparation method and application thereof
The single-atom cobalt-doped carbon fiber material prepared by electrospinning, as a three-dimensional conductive potassium metal matrix, solves the problem of potassium dendrite growth in potassium metal batteries, achieving high cycle stability of potassium metal anodes and improving battery safety. .
Patent Information
- Application Number
- CN202411493631.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
During the reaction process, existing potassium metal batteries cause more parasitic reactions between potassium and electrolytes, which aggravates the growth of potassium dendrites, affects capacity stability and causes safety problems during battery operation. .
Single-atom cobalt-doped carbon fiber materials are prepared using electrospinning methods. The material has a multi-layer porosity interconnected carbon fiber network structure. Single-atom cobalt is evenly dispersed in the carbon fiber and serves as a three-dimensional conductive potassium metal matrix, buffering volume changes and providing a conductive network. , inhibit dendrite growth.
Through the single atomic cobalt doped carbon fiber material, the cycle stability of the potassium metal negative electrode is significantly improved, the growth of the Zhi crystal is suppressed, and the safety and energy storage density of the battery is enhanced.
Smart Images

Figure CN119352195A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and in particular relates to a single-atom cobalt-doped carbon fiber material and a preparation method and application thereof. Background Art
[0002] With the rapid development of portable electronics, electrified transportation, and smart grids, lithium-ion batteries face huge consumer demand. Therefore, the development of an alternative battery system has aroused great interest among scientists and industry. For example, potassium-ion batteries have attracted widespread attention due to their comparable operating voltage and power density to lithium-ion batteries. More importantly, potassium resources are highly abundant and almost inexhaustible. These advantages give potassium-ion batteries great potential for large-scale energy storage applications and are considered to be one of the more promising alternatives to lithium-ion batteries.
[0003] Among the negative electrode materials of potassium ion batteries, metallic potassium has the lowest redox potential (-2.93 V vs SHE) and high specific capacity (687 mAh g -1 ), which helps to achieve high specific energy in potassium-based batteries. In addition, potassium metal anodes will also open up opportunities for new high-energy battery systems such as KS, K-O2 and K-Br, which can significantly improve the energy storage density. Although potassium metal batteries have many attractive properties, they have not yet been commercialized due to unresolved issues such as potassium dendrite growth, unstable solid electrolyte interface (SEI) and large volume changes of potassium anode during cycling. During the reaction process, uneven potassium deposition and volume changes often destroy the fragile SEI layer, resulting in more parasitic reactions between potassium and electrolyte, aggravating potassium dendrite growth, and ultimately leading to capacity decay and causing safety issues in battery operation (including fire and explosion).
[0004] Slowing down or inhibiting the growth of dendrites is crucial for the development of potassium metal anodes. Three-dimensional conductive carbon-based hosts have good prospects in the application of potassium metal anodes. Their advantages are: (1) potassium metal can be encapsulated in the host, thereby reducing the chance of side reactions between alkali metals and electrolytes; (2) the host can improve the structural stability of the metal anode by buffering volume changes; (3) the host can provide a conductive network to induce rapid ion / electron transfer, reduce local current density, and further hinder dendrite growth. In addition, the surface of the single-atom cobalt-doped carbon fiber host has abundant and uniformly dispersed potassium-philic sites, which is conducive to the uniform electroplating of potassium, thereby improving the cycle stability of the battery.
[0005] Therefore, the present invention proposes a single-atom cobalt-doped carbon fiber material and a preparation method and application thereof. A carbon fiber material with uniformly dispersed single-atom cobalt is prepared by electrospinning, and the content of single-atom cobalt is 1.0wt% to 9.0wt%. The carbon fiber material has an interconnected carbon fiber network with multi-layer porosity, which is beneficial to maintaining the accessibility of single-atom cobalt sites and inhibiting their agglomeration, thereby guiding uniform potassium nucleation and growth, thereby inhibiting the formation of dendrites at the potassium negative electrode; the prepared single-atom cobalt-doped carbon fiber / potassium composite negative electrode has super strong cycle stability. Summary of the invention
[0006] The purpose of the present invention is to provide a single-atom cobalt-doped carbon fiber material and a preparation method and application thereof, so as to solve the problem that in the prior art potassium metal battery mentioned in the above background technology, more parasitic reactions occur between potassium and electrolyte due to uneven potassium deposition and volume change during the reaction process, which aggravates the growth of potassium dendrites, affects capacity decay and causes safety problems in battery operation.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a single-atom cobalt-doped carbon fiber material, which has an interconnected carbon fiber network structure with multi-layer porosity, and the interconnected carbon fiber network structure is doped with uniformly dispersed single-atom cobalt; the content of single-atom cobalt is 1.0wt% to 9.0wt%.
[0009] A second aspect of the present invention provides a method for preparing a single-atom cobalt-doped carbon fiber material, comprising the following steps:
[0010] (1) Dissolving Zn(NO3)2.6H2O and Co(NO3)2.6H2O in methanol to form solution A, dissolving 2-methylimidazole in methanol to form solution B, pouring solution A into solution B, stirring, and then standing; washing the product obtained after standing by centrifugation, and then vacuum drying to obtain Co-ZIF8;
[0011] (2) adding Co-ZIF8 to N,N-dimethylformamide (DMF) for ultrasonic dispersion, adding polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) and stirring to obtain a precursor solution;
[0012] (3) preparing a fiber membrane from the precursor solution by an electrospinning method;
[0013] (4) After the fiber membrane is pre-oxidized in air, it is placed in a tubular furnace for high-temperature carbonization in an argon atmosphere to finally obtain a single-atom cobalt-doped carbon fiber material.
[0014] Preferably, the step (1) is specifically as follows:
[0015] The concentrations of Zn(NO3)2.6H2O and Co(NO3)2.6H2O in solution A are 0.1-0.5M and 0.01-0.05M respectively; the concentration of 2-methylimidazole in solution B is 0.2-1.0M;
[0016] The product is centrifugally cleaned and then vacuum dried, specifically, at a centrifugal speed of 5000-10000 r / min, a drying temperature of 50-80° C., and a drying time of 12-36 h.
[0017] Preferably, the step (2) is specifically as follows:
[0018] The mass fraction of the Co-ZIF8 in N,N-dimethylformamide (DMF) is 5wt% to 15wt%;
[0019] The ultrasonic time is 0.5 to 2 hours;
[0020] The mass fractions of polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) in N,N-dimethylformamide (DMF) are 5wt% to 12wt% and 1wt% to 4wt% respectively;
[0021] The stirring temperature is 50-70° C., and the stirring time is 8-24 hours.
[0022] Preferably, the step (3) is specifically as follows:
[0023] The electrospinning method is specifically as follows: the propulsion speed is 0.2-1.5 mL / h, the spinning voltage is 13-22 kV, the receiving distance is 10-20 cm, the temperature is 20-40° C., and the humidity is 30-60%.
[0024] Preferably, the step (4) is specifically as follows:
[0025] The pre-oxidation temperature is 200-280°C, the heating rate is 2-6°C / min, and the insulation time is 1-3h; the high-temperature carbonization temperature is 800-1100°C, the heating rate is 2-6°C / min, and the insulation time is 1-6h.
[0026] The third aspect of the present invention proposes the use of single-atom cobalt-doped carbon fiber materials in potassium metal negative electrodes.
[0027] Single-atom cobalt-doped carbon fiber material is made into an anode, and potassium metal is made into a cathode. The anode and cathode are immersed in a potassium ion electrolyte, and current is loaded at both poles to obtain a single-atom cobalt-doped carbon fiber / potassium composite negative electrode by an electrochemical deposition method.
[0028] Preferably, the single-atom cobalt-doped carbon fiber material is cut into discs as anodes, and the potassium metal is rolled and punched into discs of the same size as cathodes.
[0029] Preferably, the anode and cathode are assembled into a button cell and electrochemical deposition is performed in a glove box (water and oxygen content is less than 0.01 ppm).
[0030] Preferably, the potassium ion electrolyte is an electrolyte containing KPF6 or KTFSI, the concentration of potassium ions in the electrolyte is 0.8-4M, and the organic solvent in the electrolyte is one or more of EC (ethylene carbonate), DEC (diethyl carbonate), EMC (ethyl methyl carbonate), and DMC (dimethyl carbonate);
[0031] Preferably, the current is 0.1-0.4 mA cm -2 The deposition time of the electrochemical deposition method is 10 to 50 hours. The electrochemical deposition time is controlled by the amount of potassium metal to be deposited. For example, if 1 mAh cm -2 of potassium metal at 0.2 mA cm -2 At a current density of 5 h, the deposition time is 5 h. The deposition amount is 0.5 to 10 mAh cm -2 .
[0032] The fourth aspect of the present invention provides a potassium ion battery, comprising a single-atom cobalt-doped carbon fiber / potassium composite negative electrode, an electrolyte, a separator and a PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride) positive electrode. The operating voltage is 1.5 to 3.5 V, and the charge and discharge current density is 50 to 2000 mA g -1 .
[0033] Preferably, the electrolyte is an electrolyte containing KPF6 or KTFSI, the concentration of potassium ions in the electrolyte is 0.8 to 4M, and the organic solvent in the electrolyte is one or more of EC (ethylene carbonate), DEC (diethyl carbonate), EMC (ethyl methyl carbonate), and DMC (dimethyl carbonate).
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The single-atom cobalt-doped carbon fiber material prepared in the present invention acts as a three-dimensional conductive potassium metal matrix, which buffers the large volume change of potassium metal during the potassium plating / stripping process and enhances the stability of the structure. At the same time, they can provide a conductive network, induce rapid charge transfer and reduce local current density, thereby slowing down the growth of dendrites.
[0036] (2) The single-atom cobalt-doped carbon fiber material prepared in the present invention has single-atom cobalt confined in the carbon fiber matrix, which has maximum atomic utilization, tunable electronic structure and surface properties, and serves as a uniform potassium-philic site to achieve uniform potassium electroplating.
[0037] (3) In the present invention, zinc nitrate hexahydrate (Zn(NO3)2.6H2O), cobalt nitrate hexahydrate (Co(NO3)2.6H2O), 2-methylimidazole and methanol are used as raw materials to prepare Co-ZIF8, and then Co-ZIF8, polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) are added to N,N dimethylformamide (DMF) to prepare a precursor solution, and finally the precursor solution is prepared into a fiber film by an electrospinning method and carbonized to obtain a single-atom cobalt-doped carbon fiber material. The preparation method is simple and controllable, low-cost, and the raw materials are easily available, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a scanning electron microscope (SEM) image of the single-atom cobalt-doped carbon fiber material in Example 1 of the present invention;
[0039] Figure 2 is the X-ray diffraction (XRD) pattern of the single-atom cobalt-doped carbon fiber material in Example 1 of the present invention;
[0040] Figure 3 This is a scanning transmission electron microscope (STEM) image of the single-atom cobalt-doped carbon fiber material in Example 1 of the present invention;
[0041] Figure 4 This is a cycle performance diagram of a single-atom cobalt-doped carbon fiber / potassium composite negative electrode symmetrical battery in Example 1 of the present invention;
[0042] Figure 5 The electrochemical performance of the single-atom cobalt-doped carbon fiber / potassium composite negative electrode / PTCDA battery at different rates in Example 1 of the present invention;
[0043] Figure 6 This is a rate performance diagram of the carbon fiber / potassium composite negative electrode symmetrical battery in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Embodiment 1:
[0046] Preparation method of single-atom cobalt-doped carbon fiber material:
[0047] (1) 3.6 g Zn(NO3)2.6H2O and 0.35 g Co(NO3)2.6H2O were dissolved in 48 mL methanol to form solution A, and 4 g 2-methylimidazole was dissolved in 96 mL methanol to form solution B. Solution A was poured into solution B and stirred rapidly for 5 min and allowed to stand for 24 h. Then, the mixture was washed by centrifugation at 7000 r / min with methanol and dried in a vacuum oven at 60 °C for 12 h to obtain Co-ZIF8;
[0048] (2) 1.0 g Co-ZIF8 was ultrasonicated in 10 mL DMF for 1 h, and then 1.0 g PAN and 0.2 g PVP were added and stirred at 60 °C for 12 h to form a uniform and stable precursor solution;
[0049] (3) taking 10 mL of the precursor solution for electrospinning at a propulsion speed of 0.8 mL / h, a spinning voltage of 16 kV, a receiving distance of 18 cm, a temperature of 25 ° C, and a humidity of 50% to obtain a spun film;
[0050] (4) The obtained spun film was pre-oxidized in air at 200°C for 2 h, with a heating rate of 5°C / min. After pre-oxidation, the film was carbonized in a tubular furnace at 900°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min, to finally obtain a single-atom cobalt-doped carbon fiber material.
[0051] The scanning electron microscope (SEM) image of the single-atom cobalt-doped carbon fiber is shown in Figure 2. Figure 1 shown. Figure 1 In the process, the carbon fiber materials are cross-linked with each other and the surface has uniformly dispersed Co-ZIF8 particles. The material was tested by X-ray diffraction (XRD). Figure 2 It can be seen that there is no diffraction peak of cobalt, indicating that cobalt exists in the form of single atoms. The material was characterized by scanning transmission electron microscopy (STEM). Figure 3 It can be seen that single atomic cobalt is evenly dispersed on the surface of the carbon fiber material.
[0052] The application of single-atom cobalt-doped carbon fiber materials in the negative electrode of potassium metal batteries is as follows:
[0053] The single-atom cobalt-doped carbon fiber prepared above was cut into a 10 mm diameter disc as the anode, and a 10 mm diameter potassium metal disc as the cathode. They were assembled into a button cell in a glove box (water and oxygen contents were both less than 0.01 ppm) for electrodeposition. The electrolyte was 4 M KTFSI dissolved in EMC (diethyl carbonate), and the constant current was 0.2 mA cm -2After 30 hours of deposition, a single-atom cobalt-doped carbon fiber / potassium composite electrode was obtained. The single-atom cobalt-doped carbon fiber / potassium composite negative electrode was used as the counter electrode and working electrode of the button battery, the separator was glass fiber, and the electrolyte was 4M KFSI dissolved in EMC (diethyl carbonate). The cycle performance of potassium deposition and stripping was measured in an environment of 25±1℃.
[0054] Figure 4 The cycling performance of the single-atom cobalt-doped carbon fiber / potassium composite negative electrode symmetric battery. -2 , with a surface capacity of 0.5 mAh cm -2 The prepared materials have excellent performance under all conditions and can stably cycle for 1000 h, indicating that the prepared materials have a good inhibitory effect on dendrite growth.
[0055] The application of potassium metal battery negative electrode in potassium ion battery is as follows:
[0056] The prepared single-atom cobalt-doped carbon fiber / potassium composite negative electrode and PTCDA positive electrode battery were assembled into a potassium ion battery. The separator was glass fiber and the electrolyte was 4M KFSI dissolved in EMC. The electrochemical performance at different rates was tested. Its operating voltage was 1.5-3.5V, and the charge and discharge current density was 50-2000mA g -1 .
[0057] Figure 5 The electrochemical performance at different rates. When the charge and discharge current densities are 50, 100, 200, 400, 800, 1000, 1500 and 2000 mA g -1 When the battery capacity is 132.2, 130.5, 128.6, 126.9, 125.2, 124.6, 123.7 and 122.8 mAh g -1 When the charge and discharge current density is 200mA g -1 When the battery capacity is restored to 127.5 mAhg -1 , and still be able to circulate stably.
[0058] Embodiment 2:
[0059] The difference from Example 1 is that the preparation method of single-atom cobalt-doped carbon fiber material is:
[0060] (1) 1.6 g Zn(NO3)2.6H2O and 0.8 g Co(NO3)2.6H2O were dissolved in 80 mL methanol to form solution A, and 3.7 g 2-methylimidazole was dissolved in 80 mL methanol to form solution B. Solution A was poured into solution B and stirred rapidly for 30 min and allowed to stand for 12 h. Then, the mixture was washed by centrifugation at 8000 r / min with methanol and dried in a vacuum oven at 70 °C for 12 h to obtain Co-ZIF8;
[0061] (2) 0.6 g Co-ZIF8 was ultrasonicated in 10 mL DMF for 1 h, and then 0.8 g PAN and 0.3 g PVP were added and stirred at 60 °C for 24 h to form a uniform and stable precursor solution;
[0062] (3) taking 10 mL of the precursor solution for electrospinning at a propulsion speed of 0.6 mL / h, a spinning voltage of 15 kV, a receiving distance of 16 cm, a temperature of 25 ° C, and a humidity of 40% to obtain a spun film;
[0063] (4) The obtained spun film was pre-oxidized at 230°C in air for 2 h, with a heating rate of 5°C / min. After pre-oxidation, the film was carbonized at 1000°C in a nitrogen atmosphere in a tubular furnace for 2 h, with a heating rate of 5°C / min, to finally obtain a single-atom cobalt-doped carbon fiber material.
[0064] Embodiment 3:
[0065] The difference from Example 1 is that the preparation method of single-atom cobalt-doped carbon fiber material is:
[0066] (1) 5.2 g Zn(NO3)2.6H2O and 1.6 g Co(NO3)2.6H2O were dissolved in 60 mL methanol to form solution A, and 5.4 g 2-methylimidazole was dissolved in 100 mL methanol to form solution B. Solution A was poured into solution B and stirred rapidly for 60 min and allowed to stand for 18 h. Then, the solution was washed by centrifugation at 6000 r / min with methanol and dried in a vacuum oven at 60 °C for 18 h to obtain Co-ZIF8;
[0067] (2) 0.8 g Co-ZIF8 was ultrasonicated in 10 mL DMF for 1 h, and then 0.9 g PAN and 0.1 g PVP were added and stirred at 60 °C for 12 h to form a uniform and stable precursor solution;
[0068] (3) taking 10 mL of the precursor solution for electrospinning at a propulsion speed of 1 mL / h, a spinning voltage of 18 kV, a receiving distance of 18 cm, a temperature of 25 ° C, and a humidity of 45% to obtain a spun film;
[0069] (4) The obtained spun film was pre-oxidized at 250°C in air for 2 h, with a heating rate of 2°C / min. After pre-oxidation, the film was carbonized at 800°C in a nitrogen atmosphere in a tubular furnace for 2 h, with a heating rate of 3°C / min, to finally obtain a single-atom cobalt-doped carbon fiber material.
[0070] Comparative Example 1:
[0071] The steps and parameters are similar to those in Example 1, except that there is no Co(NO3)2.6H2O in the preparation process, and a carbon fiber material is prepared.
[0072] The carbon fiber prepared above was cut into a 10 mm diameter disc as the anode, and a 10 mm diameter potassium metal disc as the cathode. They were assembled into a button cell in a glove box (water and oxygen contents were both less than 0.01 ppm) for electrodeposition. The electrolyte was 4 M KTFSI dissolved in EMC (diethyl carbonate), and the constant current was 0.2 mA cm -2 After 30 hours of deposition, the carbon fiber / potassium composite electrode was obtained. The carbon fiber / potassium composite negative electrode was used as the counter electrode and working electrode of the button cell, the separator was glass fiber, and the electrolyte was 4MKFSI dissolved in EMC (diethyl carbonate). The cycle performance of potassium deposition and stripping was measured in an environment of 25±1℃.
[0073] Figure 6 The cycling performance diagram of the carbon fiber / potassium composite negative electrode symmetric battery. At a current density of 0.5 mA cm -2 , with a surface capacity of 0.5 mAh cm -2 The short circuit occurred after only 60 h of stable cycling, indicating severe dendrite growth.
[0074] In summary, the present invention prepares single-atom cobalt-doped carbon fiber materials through Examples 1-3, and the content of single-atom cobalt in the single-atom cobalt-doped carbon fiber materials is 1.0wt% to 9.0wt%, and has an interconnected carbon fiber network with multi-layer porosity. And through the performance comparison of the carbon fiber / potassium composite negative electrode symmetrical battery in the comparative example, it can be seen that the single-atom cobalt-doped carbon fiber material prepared by the present invention can inhibit dendrite growth and improve cycle stability, and has a good guiding significance in the application of potassium metal battery negative electrode. This method is conducive to the large-scale application of dendrite-free potassium metal negative electrode.
[0075] The above description is only used to help understand the method of the present invention and its core essence, but the protection scope of the present invention is not limited thereto. For those skilled in the art in the art, equivalent replacement or change according to the technical solution and inventive concept of the present invention within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A single-atom cobalt-doped carbon fiber material, characterized in that: The single-atom cobalt-doped carbon fiber material has an interconnected carbon fiber network structure with multi-layer porosity, wherein the interconnected carbon fiber network structure is doped with uniformly dispersed single-atom cobalt; the content of the single-atom cobalt is 1.0wt% to 9.0wt%.
2. A method for preparing the single-atom cobalt-doped carbon fiber material according to claim 1, characterized in that: The following steps are involved: (1) Dissolving Zn(NO3)2.6H2O and Co(NO3)2.6H2O in methanol to form solution A, dissolving 2-methylimidazole in methanol to form solution B, pouring solution A into solution B, stirring, and then standing; washing the product obtained after standing by centrifugation, and then vacuum drying to obtain Co-ZIF8; (2) adding Co-ZIF8 to N,N-dimethylformamide for ultrasonic dispersion, and then adding polyacrylonitrile and polyvinyl pyrrolidone and stirring to obtain a precursor solution; (3) preparing a fiber membrane from the precursor solution by an electrospinning method; (4) After the fiber membrane is pre-oxidized in air, it is placed in a tubular furnace for high-temperature carbonization in an argon atmosphere to finally obtain a single-atom cobalt-doped carbon fiber material.
3. The method for preparing a single-atom cobalt-doped carbon fiber material according to claim 2, characterized in that: The step (1) is specifically as follows: The concentrations of Zn(NO3)2.6H2O and Co(NO3)2.6H2O in solution A are 0.1-0.5M and 0.01-0.05M respectively; the concentration of 2-methylimidazole in solution B is 0.2-1.0M; The product is centrifugally cleaned and then vacuum dried, specifically, at a centrifugal speed of 5000-10000 r / min, a drying temperature of 50-80° C., and a drying time of 12-36 h.
4. The method for preparing a single-atom cobalt-doped carbon fiber material according to claim 2, characterized in that: The step (2) is specifically as follows: The mass fraction of the Co-ZIF8 in N,N-dimethylformamide is 5wt% to 15wt%; The ultrasonic time is 0.5 to 2 hours; The mass fractions of the polyacrylonitrile and polyvinyl pyrrolidone in N,N-dimethylformamide are 5wt% to 12wt% and 1wt% to 4wt% respectively; The stirring temperature is 50-70° C., and the stirring time is 8-24 hours.
5. The method for preparing a single-atom cobalt-doped carbon fiber material according to claim 2, characterized in that: The step (3) is specifically as follows: The electrospinning method is specifically as follows: the propulsion speed is 0.2-1.5 mL / h, the spinning voltage is 13-22 kV, the receiving distance is 10-20 cm, the temperature is 20-40° C., and the humidity is 30-60%.
6. The method for preparing a single-atom cobalt-doped carbon fiber material according to claim 2, characterized in that: The step (4) is specifically as follows: The pre-oxidation temperature is 200-280°C, the heating rate is 2-6°C / min, and the insulation time is 1-3h; the high-temperature carbonization temperature is 800-1100°C, the heating rate is 2-6°C / min, and the insulation time is 1-6h.
7. An application of a single-atom cobalt-doped carbon fiber material prepared by the preparation method according to any one of claims 2 to 6 in a potassium metal negative electrode, characterized in that: Single-atom cobalt-doped carbon fiber material is made into an anode, and potassium metal is made into a cathode. The anode and cathode are immersed in a potassium ion electrolyte, and current is loaded at both poles to obtain a single-atom cobalt-doped carbon fiber / potassium composite negative electrode by an electrochemical deposition method.
8. The use of a single-atom cobalt-doped carbon fiber material in a potassium metal negative electrode according to claim 7, characterized in that: The potassium ion electrolyte is an electrolyte containing KPF6 or KTFSI, the concentration of potassium ions in the electrolyte is 0.8-4M, and the organic solvent in the electrolyte is one or more of ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; The current size is 0.1-0.4 mA cm -2 ; The deposition time of the electrochemical deposition method is 10 to 50 hours.
9. A potassium ion battery, characterized in that: The invention comprises the single-atom cobalt-doped carbon fiber / potassium composite negative electrode as claimed in claim 7 or 8, an electrolyte, a separator and a 3,4,9,10-perylenetetracarboxylic dianhydride positive electrode.
Citation Information
Patent Citations
Dendrite-free potassium metal electrode with long cycle life and preparation method and application thereof
CN108649181A
Nitrogen-cobalt-doped hollow carbon nanofiber, preparation method and application thereof and metal-air battery
CN110336049A
Preparation method for nitrogen-cobalt-oxygen tri-doped network-like carbon material used as negative electrode of potassium ion battery
CN110797535A
Cobalt monatomic loaded nitrogen-doped carbon oxygen reduction catalyst and preparation method thereof
CN111468167A
Porous carbon-based nanofiber thin film material loaded by metal monatomic and metal derivative thereof as well as preparation method and application thereof
CN113540478A